1985
DOI: 10.1346/ccmn.1985.0330310
|View full text |Cite
|
Sign up to set email alerts
|

Small-Angle X-Ray Powder Diffraction, Morphology, and Structure of Allophane and Imogolite

Abstract: Abstract--Small-angle X-ray powder diffraction analyses and high-resolution electron microscopy of allophane samples (SiOJAlzO3 ratio, 1.12 to 1.68) showed that allophanes consist of nearly identical spherical particles with diameters of about 40 A and retain their characteristic "hollow" spherical morphology at different ambient moisture and even after dehydroxylation by heating at 500* to 6000C. Unheated allophane samples gave another X-ray powder diffraction band whose maximum position varied from 12.3 to 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0

Year Published

1988
1988
2009
2009

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(45 citation statements)
references
References 18 publications
3
41
0
Order By: Relevance
“…The infrared spectrum supplied by K. Wada is similar to published spectra (Russell et al, 1969), and the XRD pattern is identical to that reported for imogolite from the same location (Brown, 1980), with the same low-angle features as found by Van der Gaast et al (1985).…”
Section: Methodssupporting
confidence: 79%
See 3 more Smart Citations
“…The infrared spectrum supplied by K. Wada is similar to published spectra (Russell et al, 1969), and the XRD pattern is identical to that reported for imogolite from the same location (Brown, 1980), with the same low-angle features as found by Van der Gaast et al (1985).…”
Section: Methodssupporting
confidence: 79%
“…Such a mechanism, however, de- pends on cleavage of the tubes at an early stage, although this is incompatible with the observation of Russell et al (1969) that the tubular structure survives dehydroxylation at 700~ More recent work (Van der Gaast et aL, 1985, Wilson et aL, 1988 suggests that breakdown of the tubes may have begun at about the onset of dehydroxylation, even though the threadlike habit was preserved in the early stages. CONCLUSIONS 1.…”
Section: Implications For the Structure Of Imogolite And Its Dehydroxmentioning
confidence: 91%
See 2 more Smart Citations
“…Si-rich allophanes with Al/Si ratios close to unity are represented by the Ok, VA, and Kk samples. Ok and VA originated from weathered andesitic ashes (Yoshinaga and Aomine, 1962;van der Gaast et al, 1985), and Kk from weathered andesitic lapilli (Parfitt et al, 1980). Natural imogolite KiG has been sampled with the KiP allophane (van der Gaast et at., 1985).…”
Section: Methodsmentioning
confidence: 99%